Src nuclear localization and its prognostic relevance in human osteosarcoma. Issue 2 (17th August 2017) - Urciuoli, Enrica; Coletta, Ilenia; Rizzuto, Emanuele; De Vito, Rita; Petrini, Stefania; D'Oria, Valentina; Pezzullo, Marco; Milano, Giuseppe Maria; Cozza, Raffaele; Locatelli, Franco; Peruzzi, Barbara
Abstract : Osteosarcoma is the most common malignant bone tumor in children and young adults. The identification of proteins which exhibit different subcellular localization in low‐ versus high‐risk osteosarcoma can be instrumental to obtain prognostic information and to develop innovative therapeutic strategies. Beside the well‐characterized membrane and cytoplasmic localization of Src protein, this study evaluated the prognostic relevance of its so‐far unknown nuclear compartmentalization. We analyzed the subcellular distribution of total and activated (pY418) Src in a tissue microarray including 60 osteosarcoma samples. Immunohistochemical analyses revealed a variable pattern of Src expression and localization, ranging from negative to high‐stained nuclei combined with a substantial cytoplasmic staining for total and activated forms. The analysis of Kaplan–Meier survival curves in relationship to the diverse permutations of cytoplasmic and nuclear staining suggested a correlation between Src subcellular localization and the overall survival (OS) of osteosarcoma patients. In order to explain this different subcellular localization, normal osteoblasts and three osteosarcoma cell lines were used to investigate the molecular mechanism. Once confirmed a variable Src localization also in these cell lines, we demonstrated a correlation between the N‐myristoyltransferase enzymes expression and activity and the Src nuclear content. In conclusion, these results described a so‐far unknown Src nuclear localization in osteosarcoma cells, suggesting that the combined detection of nuclear and cytoplasmic Src levels can be used as a prognostic marker for osteosarcoma patient survival. A correlation between the N‐myristoyltransferase enzymes and the Src subcellular localization was described as well. Abstract : This article described for the first time a variable subcellular localization of the tyrosine‐kinase Src in normal osteoblasts and in osteosarcoma cell lines with different aggressiveness. By studying this subcellular localization, we found that high nuclear Src staining correlates with a good‐prognosis for osteosarcoma patients. In order to define the molecular mechanism underlining this variable localization, we demonstrated that the NMT enzyme expression and activity are, at least in part, responsible in regulating Src compartmentalization.